Childhood and parental diagnostic radiological procedures and risk of childhood brain tumors - Milne, Elizabeth; Greenop, K.; Fritschi, Lin; Attia, J.; Bailey, H.; Scott, R.; Lesley, A.; Similbert, E.; Armstrong, B. (Kluwer Academic Publishers, 2014)
Purpose: Childhood brain tumors (CBT) are the second most common type of childhood cancer and the leading cause of childhood cancer mortality. Few causes of CBT are known, but parental , fetal and early life exposures are likely to be important given the early age at diagnosis of many cases. We aimed to investigate whether parents’ diagnostic radiological procedures before conception, in the mother during pregnancy or the child’s procedures were associated with an increased risk of CBT. Methods: This population-based case-control study was conducted between 2005 and 2010. Causes were identified through all the Australian pediatric oncology centres and controls via nationwide random-digit dialing; frequency-matched to cases on age, sex, and state of residence. Information on radiological exposures in the time periods of interest was obtained for 306 case and 950 control families through mailed questionnaires. Analysis used unconditional logistic regression, adjusting for matching variables and potential confounders. Results: We found no evidence of positive associations between risk of CBT overall and childhood or parental pre-pregnancy radiological procedures. Increased ORs for high-grade gliomas associated with childhood radiological procedures were based on small numbers and may be due to the reduced intensity of CTs after 2001. Future research to investigate the safety of fetal exposure to more intense procedures like C scans is needed.